Formulação de definições utilizando o método Aristotélico (Advances in Knowledge Representation, 2021)
Abstract: Definition is an important theme in Aristotle's work. There are several types of definitions and in the context of applied ontology, the formulation of textual and formal definitions should follow the Aristotelian Principles of Genus and Differentia. The paper aims to describe the Aristotelian Principles in the formulation of definitions in ontologies and demonstrating the application of the OntoDef method. Presents a brief literature review and demonstration of the OntoDef method on terms definition of the OntONeo ontology. Application of OntoDef method bring relevant contribution to the OntONeo ontology once that helped to textually define the ontology's classes woman and pregnant woman. In addition to improving textual definitions of the ontology, as the main contribution of the OntoDef method, we highlight the clarity to identify the essence of the term to be defined, establishing the necessary and sufficient conditions for each term in question.